PERANCANGAN SISTEM PENGAMBILAN KARTU UJIAN ONLINE MENGGUNAKAN FRAMEWORK CODEIGNITER - Said -; Emy Setyaningsih; Harmastuti - (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2017)
Taking the test card is part of the academic system Institut Science & Technology AKPRIND Yogyakarta and is an activity that is always done when the student before the exam. Examination card retrieval system that runs for this still use conventional system. This method is still less effective because students have to queue for a long time and also have to come to the campus directly. The proposed system research aims to facilitate students in the process of taking exam cards. System that will be developed web-based (web based), so that this system can be accessed online using both computer and smartphone devices. Research on the online card retrieval system was developed using Codeigniter (CI), one of the framework used to build a website. The development of web-based applications, CI framework has a very fast performance, easy configuration and complete documentation. This research uses waterfall diagram as research method and MySQL as database processing. Testing system conducted in this study by using black box testing method and testing the questionnaire. Black box testing aims to obtain a set of input conditions that will fully implement all the functional requirements of a program. This test concluded that the built application system can function as expected. While testing the questionnaire is done to know user acceptance or user satisfaction to the quality of the system developed. The results of the questionnaire test showed 80.24% of 82 respondents stated strongly agree that with the Online Card Exam Taking System Using Framework Codeigniter can help and provide convenience for students in the process of taking the test card.